Comparison of characteristic of iron (Fe) powder using underground explosive pressing and universal testing machine - Rosdi R.N.; Azmi N.A.; Latheef N.A.; Hilmi A.H.; Ismail A.; Syamsir A. (American Institute of Physics Inc., 2023)
The aim of this research is to study the characteristic of Iron (Fe) powder using the explosive pressing method. The result of underground explosion pressing method was compared with pressing using the Universal Testing Machine. The explosive used is commercial explosive (Emulex). The explosive is molded into shape charge to give more pressing energy. The underground explosion was conducted since confined space can give more blast energy. Green compact was sintered to strengthen the bonding between particles. Analysis of compact powder microstructure was performed using Scanning Electron Microscope (SEM). The hardness of compact powder was tested using Rockwell Digital Hardness. The result shows the hardness of compact powder for Underground Explosive Pressing is 50.7HRA, while the compact powder using Universal Testing Machine is 24.0HRA. Microstructure results show lesser porosity by using Underground Explosive Pressing. 2018 Author(s).